Navigating Smog: Legislation Addressing Children’s Right to Health in India and Pakistan - Ali, Muhammad Imran (Serikat Pengajar Hak Asasi Manusia Indonesia, 2023)
This study investigates how legal and policy frameworks in Delhi and Lahore address the right of children to a clean and healthy environment. It explores the extent to which urban environmental governance in South Asia responds to the unique vulnerabilities of children living in cities affected by persistent smog and air pollution. These environmental hazards are closely linked to long term respiratory illness, cognitive impairment, and early mortality. Despite binding commitments under the United Nations Convention on the Rights of the Child, both India and Pakistan continue to fall short in translating international obligations into domestic protections for children exposed to urban environmental harm. While earlier research has highlighted the health impacts of air pollution, this article contributes to the literature by evaluating how national laws, regulatory frameworks, and institutional responses incorporate or overlook children’s environmental rights. Using doctrinal legal research and comparative policy analysis, the study analyses statutory instruments, regulatory standards, and international human rights norms relevant to environmental protection in Delhi and Lahore. Findings demonstrate that existing legal regimes lack child specific environmental protections and do not impose clear duties on authorities to prevent or respond to pollution related health risks. Weak enforcement, fragmented institutions, and the absence of child centred accountability mechanisms contribute to systemic neglect. The article proposes a new legal approach that embeds child sensitive principles into environmental governance, including targeted legislation, enforceable pollution controls, and emergency health measures. This research advances scholarship on human rights and environmental law in the Global South by offering a normative and practical framework to reimagine state obligations. It highlights the need to shift from general environmental regulation to rights-based protections that prioritise the health and dignity of children in urban climate and pollution governance.